2001
DOI: 10.1046/j.1365-201x.2001.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate oxidation in rat hepatocytes is inhibited by foetal calf serum

Abstract: The rate of oxidation of fatty acids in mammals is minimal prior to birth. In this study, we have shown that foetal calf serum (FCS) inhibits oxidation of palmitate while serum from newborn calves is almost without effect. Foetal calf serum was also found to increase fatty acid synthesis from acetate. Uptake of laurate in mitochondria is partially dependent upon the carnitine palmitoyltransferase (CPT) I/CPT II system, while octanoate transport occurs without its participation. Comparison of the effects of FCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A previous study reported that laurate in mitochondria was associated with the carnitine palmitoyltransferase (CPT) I/CPT II 34 which could be inhibited by malonyl CoA—the first committed step in fatty acids synthesis. 35 Considering that fatty acid is positively associated with birth weight, 36 inorganic arsenic exposure may lead to low birth weight partially by affecting laurate level and, in turn, fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that laurate in mitochondria was associated with the carnitine palmitoyltransferase (CPT) I/CPT II 34 which could be inhibited by malonyl CoA—the first committed step in fatty acids synthesis. 35 Considering that fatty acid is positively associated with birth weight, 36 inorganic arsenic exposure may lead to low birth weight partially by affecting laurate level and, in turn, fatty acids.…”
Section: Discussionmentioning
confidence: 99%